The effectiveness of business continuity plan during the Covid-19 national state of disaster : a case of the Polokwane Municipality in the Limpopo Province, South Africa - Maiwashe, Rendani Sindrellar (My University, 2023)
The year 2020 has seen the world being plunged into a health crisis due to the Coronavirus (COVID-19) pandemic (WHO: 2020). Many South African industries were faced with unpleasant impact from the COVID-19 National State of Disaster that was imposed by the President of the Republic of South Africa on 15 March 2020 which resulted in some businesses ceasing trading permanently (Stats SA, 2020). Regardless of this situation, the Polokwane Municipality has an obligation to deliver core or basic services in the face of the COVID-19 national state of disaster. Business continuity took a center stage during the COVID-19 National State of Disaster in terms of business survival, meaning that the Polokwane Municipality had to find different ways to continue to function within the realities of the COVID-19 pandemic. The study evaluated whether the Business Continuity Plan (BCP) in the Polokwane Municipality is practical and realistic and whether BCP was responsive to COVID-19 National State of Disaster and lockdown regulations that were imposed as there is minimal evidence of evaluating business continuity during pandemics except in the healthcare sector. The study employed quantitative research method to gather data from participants. The study found out that, there was sufficient implementation of the BCP during the COVID-19 National State of Disaster as confirmed by 67% respondents. The study further revealed that the Polokwane Municipality did not communicate its BCP to all employees regularly. Considering these findings, the study recommends that the Municipality should conduct workshops or training on the BCP to ensure that relevant key officials clearly understand all aspects of the BCP and sharpen their skills. Although the Polokwane Municipality have the BCP, they should ensure that there is sufficient funding and other resources to ensure that implementation of the BCP is effectless and further do research to benchmark and learn from what has worked in other Municipalities for effectiveness of the BCP.
Thesis (MPAM.) -- University of Limpopo, 2024
Keywords: Business; Health crisis; Coronavirus (COVID-19); National State of Disaster; Community health services -- Business management; COVID-19; Business planning